3D-Visualization of Neurovascular Compression at the Ventrolateral Medulla in Patients with Arterial Hypertension - Manava, Panagiota; Naraghi, Ramin; Schmieder, Roland; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael M.; Buchfelder, Michael; Hastreiter, Peter (Clinical Neuroradiology, 2020)
Purpose: Controversy exists on the association of arterial hypertension (HTN) and neurovascular compression (NVC) at the ventrolateral medulla (VLM). No standardized and reproducible technique has been introduced yet for detection of NVC in HTN. This study aimed to generate, analyze and compare different results of exact reproducible anatomical 3D-representations of the VLM in patients with HTN, based on magnetic resonance imaging (MRI). Methods: A 3T scanner provided MRI (T2-constructive interference in steady state (CISS) high resolution imaging and three-dimensional Time-of-flight (3D-TOF) angiography) from the posterior fossa of 44 patients with clinical treatment-resistant HTN. Image processing consists of segmentation of the CISS data, registration and fusion of the CISS and TOF data and visualization. For each patient two 3D-visualizations (before and after fusion) were obtained. The reproduction quality of the vessels, flow-related signal variability and pulsation artifacts were analyzed and compared, using a ranking score. Results: Integrating vascular information from TOF into CISS data reduced artifacts in 3D-visualizations of exclusively processed CISS data. The quality of 3D-visualization of the vessels near the brain stem was significantly improved (p = 0.004). The results were reproducible and reliable. The quality of the 3D-presentations of neurovascular relationships at the VLM improved significantly (p < 0.001). Conclusion: The 3D-visualization of fused image data provides an excellent overview of the relationship between cranial nerves and vessels at the VLM and simplifies the detection of NVC in HTN. It provides a powerful tool for future clinical and scientific research. Although microvascular decompression (MVD) in treatment resistant HTN is not a standard procedure, it can be discussed in selected patients with intractable severe HTN.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cranial nerves; Image fusion; Image processing; MRI; Posterior fossa; Vascular compression disorders

Glymphatic System in Ocular Diseases: Evaluation of MRI Findings - Manava, Panagiota; Eckrich, C.; Luciani, F.; Schmidbauer, J.; Lell, Michael; Detmar, K. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: There is growing evidence of leakage of gadolinium in an impaired blood-retina barrier. We investigated gadolinium enhancement in different eye compartments and correlated the enhancement with specific ophthalmologic diseases. MATERIALS AND METHODS: In a prospective clinical study (ClinicalTrials.gov Identifier: NCT05035251), 95 patients (63 with and 32 without ophthalmologic disease) were examined before and after gadolinium administration (20 and 120 minutes) with heavily T2-weighted FLAIR. The cohort was divided according to the location of pathology into anterior and posterior eye compartment groups. Relative signal intensity increase in the anterior eye chamber, vitreous body with retina, optic nerve sheath, and the Meckel cave was analyzed and correlated with the final clinical diagnosis. RESULTS: In patients with a disorder in the anterior eye compartment, significant signal intensity increases were found in the central anterior eye chamber (P 20 minutes ¼ .000, P 120 minutes ¼ .000), lateral anterior eye chamber (P 20 minutes ¼ .001, P 120 minutes ¼ .005), and vitreous body with retina (P 20 minutes ¼ .02) compared with the control group. Patients with pathologies in the posterior eye compartment showed higher signal intensity levels in the central anterior eye compartment (P 20 minutes ¼ .041) and vitreous body with retina (P 120 minutes ¼ .006). CONCLUSIONS: Increased gadolinium enhancement was found in the central and lateral anterior eye compartments and the vitreous body with retina in patients with anterior eye compartment disorders 20 and 120 minutes after contrast application, suggesting impairment of the blood-aqueous barrier. In patients with a disorder in the posterior eye compartment, pathologic enhancement indicated disruption of the blood-retinal barrier that allows gadolinium to diffuse into the vitreous body with retina from posterior to anterior, opposite to the known physiologic glymphatic pathway.
CRIS-Team Scopus Importer:2022-08-05

Neurovascular compression in arterial hypertension: Correlation of clinical data to 3d-visualizations of mri-findings - Manava, Panagiota; Hastreiter, Peter; Schmieder, Roland; Jung, Susanne; Fahlbusch, Rudolf; Dörfler, Arnd; Lell, Michael; Buchfelder, Michael; Naraghi, Ramin (Open Neuroimaging Journal, 2021)
Aims: In this study, we attempted to identify clinical parameters predicting the absence or presence of Neurovascular Compression (NVC) at the Ventrolateral Medulla (VLM) in arterial hypertension (HTN) in MRI findings. Background: Cardiovascular and pulmonary afferences are transmitted through the left vagus and glossopharyngeal nerve to the brain stem and vasoactive centers. Evidence supports the association between HTN and NVC at the left VLM. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left. Several independent studies indicate a reduction of HTN after Microvascular Decompression (MVD) of the left VLM. Image processing of MRI provides comprehensible detection of NVC. HTN affects hemodynamic parameters and organs. Objective: This study analyzes and correlates clinical data and MRI findings in patients with and without NVC at the VLM in treatment resistant HTN to obtain possible selection criteria for neurogenic hypertension. Methods: In 44 patients with treatment resistant HTN, we compared MRI findings of neurovascular imaging to demographic, clinical and lifestyle data, office and 24-hour ambulatory Blood Pressure (BP), and cardiovascular imaging and parameters. Results: Twenty-nine (66%) patients had evidence of NVC at the VLM in MRI. Sixteen patients (36%) had unilateral NVC on the left side, 7 (16%) unilateral right and 6 (14%) bilateral NVC. Fifteen (34%) had no evidence of NVC at the VLM. Patients with left sided NVC were significantly younger, than those without NVC (p=0.034). They showed a statistically significant variance in daytime (p=0.020) and nighttime diastolic BP (p<0.001) as the mean arterial pressure (p=0.020). Other measured parameters did not show significant differences between the two groups. Conclusion: We suggest to examine young adults with treatment resistant HTN for the presence of NVC at VLM, before signs of permanent organ damage appear. Clinical and hemodynamic parameters did not emerge as selection criteria to predict NVC. MVD as a surgical treatment of NVC in HTN is not routine yet as a surgical treatment of NVC in HTN is not routine yet. Detection of NVC by imaging and image processing remains the only criteria to suggest MVD, which should be indicated on an individual decision.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Hypertension; Image fusion; MRI; Neuroimaging; Neurovascular compression; Ventrolateral medulla

Optimized Camera-Based Patient Positioning in CT: Impact on Radiation Exposure - Manava, Panagiota; Galster, Marco; Ammon, Josefin; Singer, Julian; Lell, Michael; Rieger, Vera (Investigative Radiology, 2023)
Objective The aim of this study was to evaluate whether a 3-dimensional (3D) camera can outperform highly trained technicians in precision of patient positioning and whether this transforms into a reduction in patient exposure. Materials and Methods In a single-center study, 3118 patients underwent computer tomography (CT) scans of the chest and/or abdomen on a latest generation single-source CT scanner supported with an automated patient positioning system by 3D camera. One thousand five hundred fifty-seven patients were positioned laser-guided by a highly trained radiographer (camera off) and 1561 patients with 3D camera (camera on) guidance. Radiation parameters such as effective dose, organ doses, CT dose index, and dose length product were analyzed and compared. Isocenter accuracy and table height were evaluated between the 2 groups. Results Isocenter positioning was significantly improved with the 3D camera (P < 0.001) as compared with visual laser-guided positioning. Absolute table height differed significantly (P < 0.001), being higher with camera positioning (165.6 ± 16.2 mm) as compared with laser-guided positioning (170.0 ± 20.4 mm). Radiation exposure decreased using the 3D camera as indicated by dose length product (321.1 ± 266.6 mGy·cm; camera off: 342.0 ± 280.7 mGy·cm; P = 0.033), effective dose (3.3 ± 2.7 mSv; camera off: 3.5 ± 2.9; P = 0.053), and CT dose index (6.4 ± 4.3 mGy; camera off: 6.8 ± 4.6 mGy; P = 0.011). Exposure of radiation-sensitive organs such as colon (P = 0.015) and red bone marrow (P = 0.049) were also lower using the camera. Conclusions The introduction of a 3D camera improves patient positioning in the isocenter of the scanner, which results in a lower and also better balanced dose reduction for the patients.
CRIS-Team Scopus Importer:2023-01-27
Keywords: diagnostic imaging; patient-centering; radiation dosage